PENILAIAN RISIKO KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJAAN Bongkar Muat DI PELABUHAN PELABUHAN HAJI-SIMEULU LABUHAN - Ade Ferza; Darmiati, Darmiati (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
The background Occupational Health and Safety (K3) is a condition in a healthy and safe job both for the job, the company as well as for the community, and the environment around the workplace. Workers at the port are very vulnerable to the dangers and risks that arise in a process that causes death, loss, disaster, loss of production, decreased product quality, and danger to the environment, especially workers in the field of loading and unloading goods at the port. The purpose of the study was to determine the safety and work risks of loading and unloading at the Labuhanhaji-Simeulu shipping port.This research is descriptive and qualitative. Research subjects are people who are used as sources of data or sources of information by researchers for the research they do with a sample of 42 people.The results of this study indicate that the identified hazards are hazards in the categories of mechanical hazards, chemical hazards, and physical hazards. OHS risk analysis shows that generally, OHS hazards occur in workers who do not wear PPE and do not follow work instructions so workers are vulnerable to OHS risks. The highest level of risk and fatal is the danger of fractures. Although this risk is rare, the most common danger is the danger of shoulder pain, because workers carry goods by placing them on their shoulders. Risk management is carried out differently depending on the risks that occur. In general, risks are overcome by ordering workers to follow work instructions, use complete PPE, and provide OHS training.